PERAN SOFTWARE AKUNTANSI DALAM EFEKTIVITAS PENYUSUNAN LAPORAN KEUANGAN (STUDI KASUS PADA KANTOR JASA AKUNTAN LILIS ARDINI BOJONEGORO) - Mohamad Djasuli; Nike Septiana, Listin (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Financial statements are a crucial component for a company because they provide information about the company's financial condition for those who need it, such as owners, investors, lenders, and management. The preparation of effective financial statements requires a systematic and accurate process. The use of accounting software is one of the solutions that is increasingly popular among companies. In this study, a qualitative method with a case study approach is used. The results of the study show that the use of Excel software at KJA Lilis Ardini allows systematic and automatic recording from the general journal to the preparation of the final financial statements. The existence of the latest Excel software provides flexibility and the ability to be tailored to the specific needs of KJA Lilis Ardini. Thus, the use of Excel software is effective in increasing efficiency and accuracy in the preparation of financial statements at KJA Lilis Ardini, which in turn supports the company's financial performance. From the results of interviews and direct observations at KJA Lilis Ardini, it can be concluded that accounting software, especially Microsoft Excel, plays an important role in improving the effectiveness of financial report preparation at KJA Lilis Ardini.